Les « faux » mariages homosexuels de Sidi Ali au Maroc : enjeux d’un scandale médiatique - Florence Bergeaud-Blackler; Victor Eck (Revue des Mondes Musulmans et de la Méditerranée)
The cases of "gay marriages" in Ksar el Kebir and then in Sidi Ali have caused an uproar in the Moroccan press. Beyond the emotions raised by the 'outrageous' mix between the respected institution of marriage and an illegal form of sexuality, this affair showed a shift of the public treatment of the homosexual question. Does this reflects a shift in the attitude of the Moroccan society vis-à-vis the homosexuality ? Is that a sign of the raise of a gay community activism for the protection of gay rights? Are the "Marriage" of Ksar el Kebir and Sidi Ali a demonstration Morocco is ready to break the taboo of homosexuality through of an homosexual "pride" ? The conclusions of our investigations in Sidi Ali, in Fez and Casabanca show that the media coverage surrounding the affairs of gay marriages has been an instrument of a strategy of a "return to morality" following the period of King Mohamed VI establishement. This paper attempts to show the local and national issues of a fake “witch hunt” in a country where the conditions for a debate on the decriminalization of homosexuality are not ready yet.